Mosques and Women in the Perspective of Qur’anic Da‘wah “A Study on the Prohibition of Menstruating Female Preachers from Entering the Mosque” - Aritonang, Idris; Khoiri, Nisful; Ramadhani, Suci (UIN Fatmawati Sukarno Bengkulu, 2025)
Surah An-Nisa, verse 43 of the Al-Qur'an, stipulates that individuals in a state of junub are forbidden from entering the mosque. Numerous fiqh and tafsir scholars subsequently associated this restriction with menstruation women, so restricting their entry into mosques. This study seeks to investigate the function of mosques and women within the context of Qur'anic da'wah, particularly on the restriction on menstrual women, notably preachers, from visiting mosques. This research is qualitative and descriptive, employing a library research methodology that entails gathering data from several scientific publications, interpretations of the Al-Qur'an, and the perspectives of ulama concerning the regulations and etiquette for menstruation women in mosques. This study seeks to link these laws to the objectives of da'wah, particularly concerning women's involvement in religious and social activities within mosques. This research indicates two perspectives on the restriction of menstruation women from attending mosques. Rigid beliefs entirely forbid menstruation women from attending mosques to preserve the sanctity of the prayer space. Conversely, lenient interpretations permit menstruation women to occupy the mosque vicinity, provided they refrain from entering the prayer area and uphold decorum in accordance with Shari'a principles. Consequently, they may continue to engage in da'wah and religious instruction activities, provided they adhere to the etiquette prescribed by Shari'a. This research is new in its Qur'anic da'wah method, which underscores the significance of inclusivity and the role of women in da'wah within mosques, while adhering to established regulations. This research's conclusions examine the stringent and lenient perspectives of the ulama concerning these regulations